Participación de los padres de familia y la expresión gráfica en los niños de la Institución Educativa Inicial N° 1039 Arbolitos del Saber, Nauta 2022 - Tafur Oliva, Gina Carol (2022)
This research has been developed with the intention of demonstrating the participation of parents and graphic expression in the children of the Initial Educational Institution No. 1039 "Arbolitos del Saber" Nauta - 2022. The study is relevant, with a cross-sectional design field. The population considered is all children and parents, starting with the initial level. Observations were used as techniques and observation guides as tools to obtain data that were previously validated by expert judgment. It was concluded that there was a significant relationship between the participation of parents and the graphic expression in the blended instruction of the children of the institution Educativa Initial N°1039 “Arbolitos del Saber” Nauta 2022”, In this reason it is validated with the Pearson correlation coefficient (r) with a value of 0.001, which is high and direct.